Internet of things for the hotel industry: a review - Magalhães, Sérgio Tenreiro de (2021)
The Internet of Things (IoT) represents an opportunity for the hotel in-dustry to increase customer satisfaction while simultaneously reducing operational costs. This paper analyses the existing knowledge on this subject, through a re-view of the relevant publications indexed by Scopus and/or ISI Web of Science, concluding that, despite the existence of many relevant patents, registered in the past few years, the published research is very limited on this topic. The restriction to publication prior to the conclusion of the patent registration process may be a justification for this fact, and, if so, the near future will bring many novelties that will help the development of the hotel industry. It is also possible to conclude from this work that the potential of IoT is not yet well explored in the hotel indus-Try, once authors frequently theorize on the use of IoT for applications that could easily be of interest for the hotel industry, but fail to identify that opportunity as a major market.